The policy transfer of community-based rehabilitation in Gulu, Uganda. Issue 10 (21st October 2020) - Brydges, Colton; Munro, Lauchlan T.
Abstract: This paper explores the influence of the community-based rehabilitation approach among international development actors in Gulu, Uganda through the lens of policy transfer. Developed by international organizations, this approach has been promoted as a meaningful way to address the needs of persons with disabilities in low-income countries. This qualitative case study consists of a questionnaire completed by representatives from 25 different organizations, in addition to semi-structured follow-up interviews with 8 development professionals. The findings indicate that the community-based rehabilitation approach has had some influence, as respondents appeared cognisant of key principles of the approach in relation to persons with disabilities. However, detailed knowledge of the approach is mainly limited to the field of health, and there were few current examples of the approach being implemented. These results illustrate the challenges of implementing community-based rehabilitation specifically, as well as broader issues related to the transfer of international policy ideas to the Global South. Points of interest: Community-based rehabilitation is a way of helping people with disabilities in low-income countries where services are limited Development organizations in Gulu, Uganda (like the local government and non-governmental organizations) think that this approach is a good way to support people with disabilities Only a few of the people interviewed for this study had a strong understanding of the community-based rehabilitation approach, and these people mostly worked in the health sector There were no examples of community-based rehabilitation programs in Gulu at the time of the study, but some projects (mostly in the health field) used some ideas drawn from the approach Local development organizations find it difficult to apply policy ideas like community-based rehabilitation, especially when they do not have consistent funding